Clinical practice guideline for screening, diagnosis and initial treatment of localized and locally advanced prostate cancer in the Peruvian Social Security (EsSalud) - Cuentas-Jara, Mariano (2021)
Background: This article summarizes the clinical practice guide (CPG) for the screening, diagnosis, and initial treatment of localized and locally advanced prostate cancer in the Social Security of Peru (EsSalud). Objective: To provide evidence-based clinical recommendations for the screening, diagnosis, and initial treatment of adults with localized and locally advanced prostate cancer in EsSalud. Methods: A guideline development group (GDG) was formed, which included specialist physicians and methodologists, who formulated clinical questions. Systematic searches of systematic reviews were conducted and - when deemed relevant - primary studies in PubMed during 2020 and 2021. Evidence was selected to answer each of the proposed clinical questions. The certainty of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic working meetings, the GEG used the GRADE methodology to review the evidence and formulate recommendations. The CPG was reviewed by external experts before its approval. Results: The CPG addressed 06 clinical questions, divided into 03 topics: screening, diagnosis, and initial treatment. Based on these questions, 08 recommendations were formulated (04 strong and 04 conditional), 10 points of good clinical practice, and 04 flow charts. Conclusion: Evidence-based recommendations were issued for the management of patients with this pathology.